High encapsulation efficiency of poloxamer-based injectable thermoresponsive hydrogels of etoposide. (September 2014) - Soni, Govind; Yadav, Khushwant S.
Abstract Context: Hydrogels are promising polymeric network capable of sustaining the release of drug but have a major limitation for encapsulation of hydrophobic drugs. Objective: This study was undertaken to encapsulate etoposide in poloxamer 407-based thermosensitive hydrogels with an aim to sustain its release. Materials and methods: Etoposide-loaded hydrogels were prepared by the cold method and optimized for encapsulation efficiency (EE) by a 32 factorial design. Poloxamer 407-poloxamer 188 hydrogel (E-P407-P188) and poloxamer 407-poly(ethylene glycol) (E-P407-PEG) hydrogel were characterized for SEM, swelling, sol–gel phase transition and injectability study. Results and discussion: In E-P407-P188 hydrogel the EE of 75% could be obtained and in E-P407-PEG hydrogels the EE was 84%. The SEM images showed a porous structure. The release of ETO was sustained up to 48 h by E-P407-PEG hydrogel and 24 h by E-P407-P188 hydrogel. The drug release was governed by first-order kinetics and followed Fickian diffusion mechanism in both the cases. Conclusion: Such injectable thermosensitive hydrogel of etoposide could be effectively used for continuous release of drug to the tumor and surrounding tissues.